Anabolic steroid use and body image psychopathology in men: Delineating between appearance- versus performance-driven motivations. (1st August 2016) - Murray, Stuart B.; Griffiths, Scott; Mond, Jonathan M.; Kean, Joseph; Blashill, Aaron J.
Highlights: We investigated the motivation for AAS use. Appearance-driven AAS use is associated with greater body image psychopathology. Appearance-motivated AAS users may be a particularly dysfunctional subgroup. Abstract: Objective: Anabolic androgenic steroid (AAS) use has been robustly associated with negative body image, and eating- and muscularity-oriented psychopathology. However, with AAS being increasingly utilized for both appearance and athletic performance-related purposes, we investigated whether comorbid body image psychopathology varies as a function of motivation for usage. Method: Self-reported motivation for current and initial AAS use was recorded amongst 122 AAS using males, alongside measures of current disordered eating and muscle dysmorphia psychopathology. Results: Those reporting AAS for appearance purposes reported greater overall eating disorder psychopathology, F (2, 118) = 7.45, p  = 0.001, ηp 2  = 0.11, and muscle dysmorphia psychopathology, F (2, 118) = 7.22, p  < 0.001, ηp 2  = 0.11, than those using AAS primarily for performance purposes. Additionally, greater dietary restraint, F (2, 116) = 3.61, p  =0.030, ηp 2  = 0.06, functional impairment, F (2, 118) = 3.26, p  = 0.042, ηp 2  = 0.05, and drive for size, F (2, 118) = 10.76, p  <0.001, ηp 2  = 0.15, was demonstrated in those using ASS for appearance purposes. Discussion: Motivation for AAS use may be important in accounting for differential profiles of body image psychopathology amongst users. Men whose AAS use is driven primarily by appearance-related concerns may be a particularly dysfunctional subgroup.